Nonwoven
Patent Information
- Application Number
- JP2020175668
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-10-19
- Publication Date
- 2025-03-04
- Estimated Expiration
- 2040-10-19
AI Technical Summary
【0008】 本発明の不織布は、圧縮力がかかった際の厚みの低減が小さく抑えられている。また、本発明の不織布は見かけ厚みを与える空間が潰れ難く、例えば体液の吸収性が良い。
Smart Images

Figure 0007638657000005 
Figure 0007638657000006 
Figure 0007638657000007
Abstract
Description
[Technical field]
[0001] The present invention relates to nonwoven fabrics. [Background technology]
[0002] Nonwoven fabrics are often used in absorbent articles such as diapers, and techniques have been developed to impart various functions to these nonwoven fabrics.
[0003] For example, Patent Document 1 describes the incorporation of a resin-bonded nonwoven fabric impregnated or coated with an adhesive into an absorbent article in order to improve the thickness recovery of the absorbent article. Specifically, the resin-bonded nonwoven fabric is disposed as a member of the absorbent article that does not come into contact with the skin. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2001-187088 A Summary of the Invention [Problem to be solved by the invention]
[0005] Among conventional nonwoven fabrics, there are some that have been made thicker than their basis weight by providing unevenness in the thickness direction, i.e., have a thick apparent thickness between the front and back surfaces. Such nonwoven fabrics tend to be soft to the touch and have a fluffy texture. However, nonwoven fabrics with a large apparent thickness may be crushed and reduced in thickness depending on the pressure of a person's weight or the like during use. Therefore, there is room for improvement from the viewpoint of ensuring sufficient texture during use. In addition, when such nonwoven fabrics are used as a member on the skin side of an absorbent body in an absorbent article, for example, the distance separating the absorbent body from the skin surface is likely to be reduced. In particular, when the nonwoven fabric has an uneven shape, the spaces in the concaves of the unevenness may be crushed, and from the viewpoint of the absorbency of body fluids (e.g., loose stool), it is desirable to improve the thickness retention of the nonwoven fabric when a compressive force is applied.
[0006] In view of the above problems, the present invention relates to a nonwoven fabric in which reduction in thickness when a compressive force is applied is kept small. [Means for solving the problem]
[0007] The present invention provides a nonwoven fabric having fusion points between fibers, comprising fibers having attached thereto a polymer having a glass transition point of 10°C or higher, having an apparent thickness of 1.5 mm or more when a load of 0.05 kPa is applied to one side using a horizontal plate, and on at least one side, the proportion of the contact area between the horizontal plate and the nonwoven fabric under a pressure of 3 kPa to the total surface area of the nonwoven fabric is 90% or less. Effect of the Invention
[0008] The nonwoven fabric of the present invention is suppressed to a small reduction in thickness when a compressive force is applied. Furthermore, the spaces that give the nonwoven fabric an apparent thickness are not easily crushed, and the nonwoven fabric of the present invention has good absorbency for body fluids, for example. [Brief description of the drawings]
[0009] [Figure 1] 1A and 1B are side views showing specific examples of the uneven shape of the nonwoven fabric of the present invention. [Diagram 2] 1 is a drawing-substitute photograph showing an enlarged view of a polymer membrane that is fixed so as to form a membrane in a minute space surrounded by fibers. [Diagram 3] FIG. 2 is a schematic diagram showing a part of an observation screen used in a method for measuring the longitudinal orientation degree of fibers, together with a square reference line. [Figure 4] FIG. 2 is a partially sectional perspective view that illustrates a specific example 1 of the uneven shape of a nonwoven fabric. [Diagram 5] 1 is a photograph in lieu of a drawing showing a plane of one side of specific example 2 of a nonwoven fabric having a concave-convex shape. [Figure 6] 6 is a partial cross-sectional view taken along the line CC of the nonwoven fabric shown in FIG. 5. [Figure 7] 6 is a partial cross-sectional view of the nonwoven fabric shown in FIG. 5 taken along the line DD. [Figure 8]6 is a photograph showing a plan view of the opposite side of the nonwoven fabric shown in FIG. 5. [Figure 9] 9 is a partial cross-sectional view taken along line EE of the nonwoven fabric shown in FIG. 8. [Figure 10] 9 is a partial cross-sectional view of the nonwoven fabric shown in FIG. 8 taken along the line FF. [Figure 11] FIG. 1 is an explanatory diagram showing a preferred embodiment of the method for producing a nonwoven fabric of the present invention, in which (A) shows the process of placing a fiber web on a male support material and pressing a female support material into the male support material from above the fiber web, (B) shows the process of pressing the female support material into the male support material to form a fiber web, (C) shows the process of removing the female support material and blowing hot air from above the shaped fiber web to fuse the fibers together, (D) shows the state of the shaped raw nonwoven fabric removed from the male support material, and (E) shows the process of spraying a polymer coating solution onto one side of the removed raw nonwoven fabric (the side onto which the hot air was blown). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] Preferred embodiments of the nonwoven fabric of the present invention will now be described. The nonwoven fabric of the present invention has fusion points between fibers (fusion points at fiber intersections). The fusion points are the parts where the fibers are bonded to each other at the contact points between the intersecting fibers by the fusion of the thermoplastic resin component of the fibers themselves. More specifically, the fusion points are formed by, for example, melting the surface of the thermoplastic fiber by heat treatment during the manufacturing process of the nonwoven fabric, and fusing the fibers together. Examples of the nonwoven fabric of the present invention include thermal bonded nonwoven fabrics, and more specifically, air-through nonwoven fabrics (nonwoven fabrics in which the fusion points are formed by hot air treatment. Short fibers of 60 mm or less are mainly used.) and spunbonded nonwoven fabrics (nonwoven fabrics in which a resin in a molten state is spun into a nonwoven fabric as it is, and the fusion points are formed by embossing. Long fibers of 100 mm or more are mainly used.) are included. When used in contact with the skin, such as in the case of materials for absorbent articles, air-through nonwoven fabrics are preferable, especially from the viewpoint of texture.
[0011] The nonwoven fabric of the present invention has one side and a second side on the opposite side opposite to the first side. The first side and the second side form the front and back sides of the nonwoven fabric of the present invention. The first side and the second side are the side furthest from the horizontal plane in the vertical direction to the horizontal plane when the nonwoven fabric is placed still on the horizontal plane, and the side closest to the horizontal plane. The first side and the second side are sometimes referred to as the first side and the second side. Which of the first side and the second side is to be the front side (usage side) is appropriately set depending on the purpose of the article. The front side is the side that receives a compressive force during use. When the nonwoven fabric of the present invention is used as a member such as a top sheet of an absorbent article, the front side is the skin side and the back side is the non-skin side. The skin side and non-skin side refer to the side facing the skin of a user, etc., and the opposite side. The skin side and non-skin side are defined as indicating a relative positional relationship even when they do not directly contact the skin of a user, etc.
[0012] The nonwoven fabric of the present invention has an apparent thickness of 1.5 mm or more under a load of 0.05 kPa. Here, the "apparent thickness" means the vertical distance between a horizontal plane and an imaginary plane (horizontal plate) that is in contact with the outermost part of the side of the nonwoven fabric opposite to the side that is in contact with the horizontal plane when the nonwoven fabric is placed on the horizontal plane (hereinafter, the vertical direction to the horizontal plane may be simply referred to as the "vertical direction"). For example, when the nonwoven fabric of the present invention has an uneven shape on both sides, the apparent thickness is the vertical distance between the position of the apex of the convexity on one side and the position of the apex of the convexity on the other side. The "apparent thickness" means the thickness when a load of 0.05 kPa is applied from one side using a horizontal plate. Specifically, it can be measured by the following method. Here, the "load of 0.05 kPa" means a load that suppresses fuzzing on the surface of the nonwoven fabric, and is a light load (a light load that is not a compressive force that would crush the thickness of the nonwoven fabric) necessary to properly measure the apparent thickness of the nonwoven fabric. The load of 0.05 kPa is applied to the nonwoven fabric by placing a horizontal plate, for example a circular plate with a diameter of 2.5 cm and a mass of 2.45 g, on one side of the nonwoven fabric.
[0013] (Method for measuring the apparent thickness of nonwoven fabric under a load of 0.05 kPa) The nonwoven fabric to be measured is cut into 10 cm x 10 cm pieces to prepare a measurement sample. Using a laser thickness gauge (high-precision displacement sensor ZS-LD80 (product name) manufactured by Omron Corporation. All laser thickness gauges used in this specification are of this type), a load of 0.05 kPa is applied to one side of the measurement sample using a horizontal plate, and the thickness is measured in this state. Measurements are taken at three locations, and the average value is regarded as the apparent thickness of the nonwoven fabric to be measured. When the nonwoven fabric to be measured is incorporated into a product, the adhesive strength of the adhesive or the like is weakened by a cooling means such as a cold spray, and the nonwoven fabric is removed from the product before the above measurement is performed. This method of removing the nonwoven fabric is similarly applied to other measurements in this specification. If it is not possible to take out a piece of nonwoven fabric measuring 10 cm x 10 cm, take out as large a piece as possible.
[0014] The nonwoven fabric of the present invention has an apparent thickness of 1.5 mm or more under a load of 0.05 kPa, so that the thickness can be felt at the beginning of use. In addition, this apparent thickness can clearly demonstrate the effect of fiber reinforcement by adhesion of a polymer having a glass transition point of 10° C. or more, which will be described later, when a compressive force is applied to the nonwoven fabric. From this viewpoint, the apparent thickness is preferably 2 mm or more, and more preferably 3 mm or more. From the viewpoints of storage efficiency and ease of processing, the apparent thickness is preferably 12 mm or less, more preferably 10 mm or less, and even more preferably 9 mm or less.
[0015] In addition, in the nonwoven fabric of the present invention, the contact area between the horizontal plate and the nonwoven fabric accounts for 90% or less of the surface area of the nonwoven fabric on at least one of the front and back sides. This contact area can be measured by the following method, applying a pressure of 3 kPa. The "surface area of the nonwoven fabric" means the area of the outline of the nonwoven fabric obtained by observing the surface of the nonwoven fabric to be measured from above. Therefore, when there are irregularities, the area of the part along the undulations is ignored. The contact area ratio of 90% or less means that at least the surface of the nonwoven fabric to be measured has an uneven shape, and crushing is suppressed under a pressure of 3 kPa as described below. Note that the pressure of 3 kPa is assumed to be the pressure applied to the back side of the diaper when the nonwoven fabric of the present invention is used as the top sheet of the diaper and a premature baby (0 years 1 month to 0 years 4 months) wearing the diaper lies on his back. The uneven shape means a shape in which convex parts protruding in the thickness direction and concave parts recessed in the thickness direction are alternately arranged in a planar direction when the nonwoven fabric is viewed in the thickness direction. In the uneven shape, it is preferable that there is a wall surface in the thickness direction connecting the first surface and the second surface, which are the front and back surfaces of the nonwoven fabric. The uneven shape is preferably present on both sides of the nonwoven fabric, not just on one side of the front and back sides. It is preferable that the proportion of the contact area on both the first and second sides, i.e., the front and back sides of the nonwoven fabric, is 90% or less. The ratio of the contact area is preferably 80% or less, and more preferably 70% or less, from the viewpoint of improving the feel, and is preferably 30% or more, more preferably 40% or more, and even more preferably 50% or more, from the viewpoint of improving the bonding strength with other members.
[0016] (Method of measuring contact area) (1) Cut a measurement sample measuring 50 mm x 50 mm from the nonwoven fabric. (2) Place the measurement sample with the measurement surface facing up. (3) Using a high-precision shape measurement system KS-1100 (product name, manufactured by Keyence Corporation), the measurement surface is irradiated with laser light to measure the surface shape (the height and depth of the thickness that rises and falls along the surface direction of the measurement surface) of the measurement surface in a no-load state (natural state without load) and an image is captured. 2 (Measurement pitch: 20 μm vertically, 20 μm horizontally), and the movement speed is 10 cm / sec. (4) Next, a transparent acrylic plate with a mass of 170 g is placed on the measurement surface of the measurement sample, and a weight with a mass of 600 g is further placed on the acrylic plate. Under this condition, a pressure of 3 kPa is applied, and the surface shape of the measurement surface is measured and an image is captured in the same manner as in (3) above. (5) The images captured in (3) and (4) above are analyzed using a shape analysis application called KS-Analyzer (product name, manufactured by Keyence Corporation). Specifically, the area where the thickness changes from the no-load state to the application of a pressure of 3 kPa (minimum measurable scale: 0.01 μm) is extracted and binarized to obtain a surface image of that area. (6) The surface image of the part where the thickness has changed obtained in (3) above is imported and processed using image processing software NewQube (Ver. 4.22, product name, manufactured by Nexus Co., Ltd.), and its area is measured. This area corresponds to the area of the part that comes into contact with the skin when the nonwoven fabric of the measurement sample is pressurized at 3 kPa, i.e., the contact area. (7) The measured area is divided by the area of the measurement sample (measurement points: 251,001 points (=501 x 501)) to calculate the "contact area ratio" of the measurement surface of the nonwoven fabric to be measured.
[0017] The nonwoven fabric of the present invention has fibers to which a polymer having a glass transition point of 10° C. or higher (hereinafter, also referred to as an attachment polymer) is attached. The attachment polymer is attached in a fixed state to the fibers constituting the nonwoven fabric, increasing the strength of the fiber surface and increasing the adhesive strength between the fibers. The fibers to which such a polymer is attached may be on the exposed surface of the nonwoven fabric of the present invention or may be inside the nonwoven fabric. As a result, when the nonwoven fabric of the present invention is used, the attachment polymer acts to maintain the positional relationship between the fibers, improving the shape and thickness retention of the nonwoven fabric. The fibers to which the attachment polymer that acts in this way are attached in the nonwoven fabric of the present invention increase the thickness retention (compression resistance) against the applied compressive force. As a result, even when a compressive force is applied, the thickness loss of the thick nonwoven fabric of the present invention is kept small. In other words, the nonwoven fabric of the present invention has a large apparent thickness between the front and back surfaces, and is capable of changing the thickness due to the application of a compressive force, while the loss of thickness when a compressive force is applied is kept small. When such a nonwoven fabric of the present invention is used as a member on the skin side of the absorbent body in an absorbent article, the distance separating the absorbent body from the skin side is maintained even when a compressive force is applied, and a space for absorbing body fluids (e.g., loose stool, etc.) can be secured. For example, loose stool, etc. is temporarily stored in the space during absorption, reducing the diffusion area in the planar direction, preventing the loose stool from adhering to the skin, and the liquid component of the loose stool smoothly transfers to the absorbent body, improving liquid absorbency. In particular, when the nonwoven fabric of the present invention has an uneven shape (for example, when both sides of the nonwoven fabric 10 in FIG. 1(A) and the nonwoven fabric 20 in FIG. 1(B) have an uneven shape, or when only one of the front and back sides has an uneven shape (not shown)), the space formed along the unevenness becomes clearer, and the above-mentioned effect becomes more prominent. In addition, in FIGS. 1(A) and (B), one surface side 1A located at the top is shown as the skin side, and the other surface side located at the bottom is shown as the non-skin side. Conventionally, when the apparent thickness of a nonwoven fabric is increased, the change in thickness is large, and the collapse is large. Also, when the apparent thickness of a nonwoven fabric is thin, the change in thickness when a compressive force is applied is small to begin with, and it is difficult to fully exert the thickness retention effect of the above-mentioned attached polymer. In contrast, the nonwoven fabric of the present invention has the above-mentioned apparent thickness and has fibers to which the attached polymer is attached, so that it can retain a thickness when a compressive force that could not be obtained conventionally is applied. Furthermore, since the nonwoven fabric of the present invention has an uneven shape and the apparent thickness, and has fibers to which the above-mentioned attachment polymer is attached, it is able to retain its thickness when a compressive force is applied, which was not possible with conventional flat nonwoven fabrics in which thickness was ensured simply by increasing the basis weight.
[0018] From the viewpoint of further enhancing the above-mentioned effects, the adhesion polymer preferably has a glass transition point of 25° C. or higher, and more preferably 40° C. or higher. From the viewpoint of availability, the adhesion polymer preferably has a glass transition point of 200° C. or lower, more preferably 150° C. or lower, and even more preferably 100° C. or lower.
[0019] (Method for measuring the glass transition temperature of the attached polymer) (1) Remove the nonwoven fabric from the product and prepare a 0.3g sample of the nonwoven fabric as a measurement sample. Next, place the nonwoven fabric sample in a beaker containing 100mL of ethyl acetate and stir for 30 minutes, remove the nonwoven fabric sample and dry it. This washes away any ingredients that were attached to the nonwoven fabric sample, such as skin care agents and hot melt adhesives. Repeat this process to prepare a total of 1.0g or more of the sample. (2) The nonwoven fabric sample is placed horizontally and the horizontal cross section is cut and cut into pieces of about 0.1 mm in length. 1.0 g of this nonwoven fabric sample is placed in a beaker and hexafluoroisopropanol (hereinafter also referred to as HFIP) is added to separate it into HFIP-insoluble and HFIP-soluble parts. This dissolves the polyethylene terephthalate (hereinafter also referred to as PET) component of the fiber. (3) The HFIP-insoluble fraction obtained in (2) is added to heated xylene at 130°C, thoroughly stirred, and filtered to separate the heated xylene-insoluble fraction and heated xylene-soluble fraction. This dissolves the polypropylene (hereinafter also referred to as PP) and polyethylene (hereinafter also referred to as PE) components of the fibers, leaving behind the cellulose-based fibers. (4) The heated xylene insoluble fraction obtained in (3) above is measured by Fourier transform infrared spectroscopy (hereinafter also referred to as FT-IR) to determine the monomer composition, and the glass transition temperature is calculated from the following Fox formula (S1) (Adhesive Handbook, 2nd Edition, p. 144, October 12, 1995, published by the Japan Adhesive Tape Industry Association). However, if a peak derived from cellulose is observed in FT-IR, that peak is not used in the calculation.
[0020]
number
[0021] In the formula, Tg represents the glass transition temperature of the deposited polymer, and Tg i indicates the glass transition temperature when monomer i is polymerized, and W i denotes the mass fraction of monomer i in the deposited polymer.
[0022] The aforementioned "polymer having a glass transition point of 10° C. or higher" has an adhesive property that allows it to be fixed and not to flow off. The attachment polymer is fixed to the surface of the fibers constituting the nonwoven fabric of the present invention. The attachment polymer is fixed to the surface of the fibers so as to form a membrane in the space surrounded by the fibers, which is formed when the fibers cross each other (for example, the attachment polymer membrane 61 formed in the space surrounded by the fibers 7 shown in FIG. 2). The surface of the fibers to which the attachment polymer is fixed includes the surface of the fusion point between the fibers. It is preferable that the attachment polymer present on the surface of the fusion point covers the outer surface of the portion where the fibers cross and overlap (the outer surface of the fused fibers). In this way, the attachment polymer increases the strength of the fiber surface at the portion where the fibers are fixed. The attachment polymer also bonds the fibers together, imparting an adhesive strength to the nonwoven fabric of the present invention that is greater than the fusion point. In particular, as shown in FIG. 2, the attachment polymer film 61 extends beyond the fusion point and increases the adhesive strength between the fibers. The attachment polymer and the fusion point can be visually distinguished using a tabletop scanning electron microscope (SEM).
[0023] The attachment polymer is a resin component different from the constituent fibers of the nonwoven fabric, and is fixed to the surface of the constituent fibers after the nonwoven fabric is made. It can be fixed to one side of the nonwoven fabric by, for example, spraying, coating, impregnation, etc. As a result, the attachment polymer is uniformly fixed over the entire one side of the nonwoven fabric of the present invention. In particular, when one side of the nonwoven fabric of the present invention has an uneven shape, spraying by spraying or impregnation is preferred from the viewpoint of fixing the attachment polymer along the uneven shape (particularly, from the viewpoint of fixing to the wall surface along the thickness direction). When the attached polymer is fixed, the coating agent before the application of the attached polymer may be applied as a 100% solution, but it is preferable to dilute it and apply it from the viewpoint of suitable control of the amount of application. Examples of the dilution liquid include water and ethanol. From the viewpoint of workability, the diluted polymer coating liquid is preferably a liquid in which the content concentration of the polymer having a glass transition point of 10° C. or more is 3% by mass or more and 55% by mass or less, and more preferably 5% by mass or more and 10% by mass or less. The coating agent before application of the adhesion polymer (hereinafter also referred to as the adhesion polymer coating agent) refers to the one before the occurrence of reactions such as crosslinking after application. The adhesion polymer coating agent is mainly solid, but may be liquid. A 100% solution of the adhesion polymer coating agent and a diluted one are called the adhesion polymer coating liquid (a solution before dilution may be called the adhesion polymer solution).
[0024] As the attachment polymer, various polymers having the above-mentioned glass transition point can be used. For example, styrene-butadiene rubber (hereinafter also referred to as SBR), (meth)acrylic polymer, vinyl acetate polymer, polyurethane, styrene polymer, etc., which have the above-mentioned glass transition point can be mentioned. Here, "(meth)acrylic polymer" means both acrylic polymer and methacrylic polymer. In the styrene-butadiene rubber, the ratio of styrene to the total mass of styrene and butadiene is preferably 60 mass % or more. In the (meth)acrylic polymer, R in the following formula (I) 2 is preferably a polymer mainly composed of a component in which R is an alkyl group having 4 or less carbon atoms, 1 is a methyl group, and R 2 It is more preferable that the polymer contains, as a main component, a methacrylic acid ester in which the alkyl group has 4 or less carbon atoms. The main component refers to the component with the largest content. In the vinyl acetate polymer, the vinyl acetate component preferably accounts for 60% by mass or more based on the total mass of all components. In the polyurethane, R in the following formula (II) 3 and R 4 It is preferable that R has an aromatic ring or a heterocyclic ring. 3 and R 4is a linking group consisting of an aromatic ring or a heterocyclic ring, and is a linking group consisting of an aromatic ring or a heterocyclic ring and another component. Examples of the aromatic ring or heterocyclic ring include benzene, thiophene, and pyridine.
[0025] [ka]
[0026] In the formula (I), R 1 represents a hydrogen atom or a methyl group, R 2 represents an alkyl group or a hydrogen atom.
[0027] [ka]
[0028] In the above formula, R 3 and R 4 represents a linking group.
[0029] Furthermore, the adhesive polymer coating agent to be fixed to the nonwoven fabric is preferably one that undergoes a crosslinking reaction (including pseudo-crosslinking) after coating to further increase the strength of the fiber surface and the adhesive strength between the fibers. More specifically, the coating agent before crosslinking is preferably one that contains a monomer having a reactive site (crosslinking site) such as a vinyl group, a methylol group, an amino group, a carboxyl group, a carbonyl group, or a sulfhydryl group.
[0030] (Method for confirming the presence of polymer attached to nonwoven fabric) (1a) The process (1) in the above (Method for measuring the glass transition temperature of the deposited polymer) is carried out. (1b) The nonwoven fabric sample is dyed using an identification reagent (Bouken Stain II fiber identification reagent, manufactured by Boken Quality Evaluation Organization, a general incorporated foundation) that dyes the attached polymer fixed to the fiber surface a color different from the fiber and distinguishes between the two. (1c) With one surface of the nonwoven fabric sample placed on a horizontal surface with one side facing up, an observation image of the exposed surface is captured at 150x magnification using a digital microscope VHX-900 (product name, manufactured by Keyence Corporation; all digital microscopes in this specification refer to this type). The captured image is the observation image. The observation image size is 1600 x 1200 pixels. (1d) The observed image is subjected to a ternary value process, and the fiber regions not covered with the attached polymer, the attached polymer regions, and other regions (such as voids between fibers) are identified by the ternary values of color to confirm the presence of the attached polymer. If the presence of the attached polymer is not observed on the first surface side, the same measurement as above is performed on the second surface side, which is the opposite surface, to confirm the presence of the attached polymer.
[0031] The details of the staining process (1b) above will now be described. (1b-1) Shake the container of Bouken Stain II well to mix thoroughly. (1b-2) Put 5 mL of the mixed Bowen Stain II into a beaker of approximately 200 mL in size, add tap water, and make the dye solution to a total volume of 100 mL. (1b-3) Heat the dye solution and add the nonwoven fabric sample when it reaches about 90°C before boiling, and boil at 95°C for 2 minutes. (1b-4) Take out the nonwoven fabric sample, rinse thoroughly with water, and then dry it. (1b-5) The color is compared with the identification color. For example, the attached polymer containing acrylic resin or styrene-butadiene rubber will be dyed red and the fiber will remain white. However, the color of the dye of the attached polymer will vary depending on the attached polymer component.
[0032] A specific example of the calculation process of (1d) above is shown below. In this example, the fiber identification reagent Bouken Stain II is used to dye the attached polymer regions containing acrylic resin or styrene-butadiene rubber red, the fiber regions remain white, and the other regions other than the attached polymer regions and the fiber regions (such as the gaps between fibers) turn black. (1d-1) The observed image is converted to three values (white, red, black). This is done by image processing on a computer, and the red area and white area are calculated in the RGB color model. (1d-2) Convert from the RGB color model to the HSV color model. In the HSV color model, red is defined as H: 0° to 60° and 270° to 360°, S: 30% to 100%, and V: 40% to 100%. White is defined as H: 0° to 360°, S: 0% to 20%, and V: 40% to 100%. Black is defined as the range other than the above. (1d-3) In this way, the red area (deposited polymer) and the white area (fiber) are calculated in the HSV color model, and the process of (1d) above is carried out.
[0033] The nonwoven fabric of the present invention has an uneven shape, and preferably has a wall surface in the thickness direction connecting the first and second surfaces, which are the front and back surfaces of the nonwoven fabric, and the attachment polymer is present on the wall surface. For example, in the uneven nonwoven fabric 10 shown in Fig. 1(A), the attachment polymer is preferably present on a slightly inclined wall surface 14 connecting the top 12A of the pyramidal protrusion 12 on the first surface side 1A and the top 13A of the pyramidal protrusion 13 on the second surface side 1B. In addition, in the uneven nonwoven fabric 20 shown in Fig. 1(B), the attachment polymer is preferably present on a vertical wall surface 24 connecting the flat top 22A of the columnar protrusion 22 on the first surface side 1A and the flat top 23A of the columnar protrusion 23 on the second surface side 1B. 1(A) and (B), one of the front and back surfaces may be uneven and the other surface may be flat. In this case, a wall surface in the thickness direction (not shown) is present at a portion connecting the top of the protrusion on one surface and the flat portion on the other surface, and the attached polymer is preferably present on the wall surface.
[0034] The wall surface has more fibers aligned in the thickness direction than the fibers on the front and back sides of the nonwoven fabric, and the fibers have a high longitudinal orientation, so it has a structure that supports the nonwoven fabric in the thickness direction. The presence of the attached polymer on such a wall surface increases the strength of the longitudinally oriented fiber surface and the shape retention of the wall surface including the fiber surface, and further increases the thickness retention (compression resistance) of the nonwoven fabric against compressive forces. Such an effect is difficult to obtain with conventional flat nonwoven fabrics in which the thickness is ensured by simply increasing the basis weight of the fiber layer oriented in the planar direction.
[0035] From the viewpoint of further improving the thickness retention of the nonwoven fabric of the present invention, the adhesion area ratio of the adhesion polymer to the wall surface is preferably 20% or more, more preferably 30% or more, and even more preferably 40% or more. From the viewpoint of improving the feel of the nonwoven fabric, the adhesion area ratio of the adhesion polymer to the wall surface is preferably 60% or less, more preferably 55% or less, and even more preferably 50% or less.
[0036] (Method for measuring the adhesion area ratio of the adhesion polymer on the wall surface) Based on the above-mentioned (method for confirming the presence of attached polymer in nonwoven fabric), the wall surface is cut out, and fiber areas not covered with attached polymer, attached polymer areas, and other areas (such as voids between fibers) are identified from the captured image of the wall surface. Specifically, three points on the wall of the nonwoven fabric stained with Bouken Stain II are photographed at 150x magnification using a digital microscope. The image size is 1600 x 1200 pixels. Next, the observed image is subjected to a ternary value process and converted from RGB to an HSV color model (under the same conditions as described above), and the number of pixels in the observed image judged to be red is regarded as the polymer adhesion area (unit: px) on the wall surface. From the obtained value, the adhesion area ratio of the adhered polymer is calculated based on the following formula (S2). Percentage of polymer adhesion area on the wall (%) = polymer adhesion area on the wall (px) ÷ total number of pixels in the image (1600px × 1200px) × 100 (S2) The average value of the three images of the wall surface is taken as the polymer adhesion area ratio on the wall surface of the nonwoven fabric being measured.
[0037] The longitudinal orientation of the fibers on the wall surface is indicated by the degree of longitudinal orientation of the fibers. The "degree of longitudinal orientation" is a value measured by the method described below (Method for measuring the degree of longitudinal orientation of fibers), and indicates the degree to which the orientation of fibers having a thickness direction component is uniform. The term "fibers having a thickness direction component" refers to fibers that have a vertical component as a vector relative to the horizontal plane when the nonwoven fabric of the present invention is placed on a horizontal plane with one of its front and back sides facing up.
[0038] From the viewpoint of improving the thickness retention of the nonwoven fabric when pressed, the degree of longitudinal orientation is preferably 50% or more, more preferably 55% or more, and even more preferably 60% or more. From the viewpoint of increasing the strength of the nonwoven fabric, the degree of longitudinal orientation is preferably 85% or less, more preferably 80% or less, and even more preferably 75% or less.
[0039] The wall surface having the above-mentioned degree of longitudinal orientation may extend along any direction of the nonwoven fabric plane. It is preferable that the wall surface extending along at least one direction has the above-mentioned degree of longitudinal orientation in the thickness direction. For example, the nonwoven fabric has MD (machine direction during manufacture) and CD (direction perpendicular to MD, cross direction), and it is preferable that the wall surface extending along at least either MD or CD has the above-mentioned degree of longitudinal orientation in the thickness direction, and it is more preferable that the wall surface extending along both MD and CD has the above-mentioned degree of orientation in the thickness direction.
[0040] (Method for measuring the degree of longitudinal orientation of fibers) (1) A nonwoven fabric sample is frozen with liquid nitrogen and placed on a horizontal plane. Then, a thickness cross section (cross section in the vertical direction) of the nonwoven fabric sample at a position that is 50% of the thickness in the vertical direction relative to the horizontal plane (the center of the thickness) is prepared by cutting with a razor blade. (2) The thickness cross section is observed at 35x magnification using a SEM, and an observed image is taken. (3) A reference line L forming a square of 0.5 mm x 0.5 mm (dimensions within the observed image) is added to the observed image. Here, the reference line L is composed of an upper side L1 and a lower side L2 that are aligned with the direction along the horizontal plane, and a left side L3 and a right side L4 that are aligned with the vertical direction. (4) Count the total number of fibers passing through the reference line formed by each side of the square. The total number of fibers passing through the reference line L of the top and bottom sides L1 and L2 of the square is the "top and bottom fiber count," and the total number of fibers passing through the reference line L of the left and right sides L3 and L4 of the square is the "left and right fiber count." (5) The degree of longitudinal orientation Q of fibers in a nonwoven fabric is calculated as (number of upper and lower fibers) / (number of upper and lower fibers + number of left and right fibers)×100. Three observation images of each of these were prepared and measured for the same nonwoven fabric sample, and the average was used as the measurement data. 3 shows an observation screen with a square reference line L. In the drawing, black dots 71 are positions where the fiber 7 passes through the reference line L (L1 to L4).
[0041] The "thickness center" refers to a portion between a horizontal plane and an imaginary plane in the "apparent thickness" of the nonwoven fabric defined above, the portion being 50% of the distance in the vertical direction to the horizontal plane. The apparent thickness of the nonwoven fabric here is measured based on the above-mentioned (method of measuring the apparent thickness of a nonwoven fabric under a load of 0.05 kPa).
[0042] The nonwoven fabric of the present invention is suppressed to a small reduction in thickness when a compressive force is applied. From the viewpoint of ensuring a sufficient thickness during use, the apparent thickness of the nonwoven fabric of the present invention when compressed at 3 kPa is preferably 1.5 mm or more, more preferably 1.8 mm or more, and even more preferably 2.0 mm or more. As a result, the nonwoven fabric of the present invention has a thickness that can be felt even when it is pressed and used, and has a comfortable texture. Furthermore, when the nonwoven fabric of the present invention is used as a member on the skin side of the absorbent body in an absorbent article, the distance and space between the absorbent body and the skin surface can be more effectively secured during use. For example, even if a baby excretes loose stools while sleeping, the diffusion area of the loose stools in the planar direction is reduced, the adhesion of the loose stools to the skin is suppressed, and absorbency is improved. Moreover, the apparent thickness of the nonwoven fabric of the present invention when pressed at 3 kPa is preferably 5 mm or less, more preferably 4 mm or less, and even more preferably 3 mm or less, from the viewpoint of improving liquid absorbency.
[0043] The apparent thickness at a pressure of 3 kPa can be measured by changing the load in the above-mentioned (method for measuring the apparent thickness of a nonwoven fabric under a load of 0.05 kPa) to 3 kPa and leaving the material to stand for 1 minute with the load (compressive force) applied.
[0044] In the nonwoven fabric of the present invention, the content of the above-mentioned adhesion polymer is 100 g / m per unit area of the nonwoven fabric from the viewpoint of improving the feel of the nonwoven fabric. 2 Less than 80 g / m is preferable. 2 Less than 50 g / m is more preferable. 2 The content of the above-mentioned adhesion polymer is more preferably 15 g / m2 per unit area of the nonwoven fabric from the viewpoint of improving the thickness retention of the nonwoven fabric when pressed. 2 More than 20 g / m is preferable. 2 More preferably, 25 g / m 2 The above is more preferable.
[0045] In addition, in the nonwoven fabric of the present invention, in order to have a thickness before and after pressing as described above, and to have a soft and flexible feel, the basis weight is 100 g / m 2 Less than 80 g / m is preferable. 2 Less than 60 g / m is more preferable. 2 The following is even more preferred: The lower limit of the basis weight is not particularly limited, but from the viewpoint of improving the texture of the nonwoven fabric, it is set to 10 g / m 2More than 15g / m is preferable. 2 More preferably, 20 g / m 2 The above is more preferable.
[0046] When the nonwoven fabric of the present invention 1 has an uneven shape, various uneven shapes can be used. In addition, various materials that are usually used as materials that come into contact with the skin can be used. For example, the uneven shape of the nonwoven fabric may be of various types, such as those with solid convexities, those with hollow convexities, those with a single fiber layer, those with a two-layer fiber layer, those with convexities arranged in a scattered manner in the planar direction, those with convexities and concaves arranged in a ridge-like pattern, etc. In addition, the uneven shape is not limited to being on one side, and may be on both sides. Among these, preferred is a nonwoven fabric having a single layer structure in which the convex portions of the concave-convex shape are hollow and the concave-convex shape is present on both sides of the nonwoven fabric, for example the following nonwoven fabric 80 (specific example 1) and nonwoven fabric 90 (specific example 2). These are explained below.
[0047] The nonwoven fabric 80 (Specific Example 1) has a single layer structure containing thermoplastic fibers, and has the uneven shape shown below. That is, it has outer surface fiber layers 81, 82 on the first side 1A and second side 1B, and a plurality of connecting portions 83 disposed between the outer surface fiber layer 1 on the first side 1A and the outer surface fiber layer 2 on the second side 1B. The outer surface fiber layer 81 on the first side 1A and the outer surface fiber layer 82 on the second side 1B are partially fused to the connecting portions 83. In addition, in the outer fiber layer 82 and the connecting portions 83 on the second surface 1B side, the attachment polymer is present on the fiber surfaces, and the attachment polymer is attached so as to cover the fiber entanglement points. The outer fiber layers 81, 82 and the connecting portion 83 form an uneven shape in the thickness direction of the nonwoven fabric 80, which includes hollow convex portions, concave portions, and wall surfaces connecting the convex portions and the concave portions. The uneven shape is formed on both the first surface 1A side and the second surface 1B side. Specifically, on the first surface 1A side, the convex portions 81 formed by the outer fiber layer 81 and the concave portions 88 between the outer fiber layers 81 have an uneven shape. On the second surface 1B side, the convex portions 82 formed by the outer fiber layer 82 and the concave portions 89 between the outer fiber layers 82 have an uneven shape. The convex portions 81 formed by the outer fiber layer 81 and the convex portions 82 formed by the outer fiber layer 82 are both hollow. The connecting portion 83 forms a wall surface 83 connecting the convex portions 81 and the concave portions 88 (the convex portions 82 and the concave portions 89). Regarding this nonwoven fabric 80, see paragraphs
[0010] to
[0030] of JP 2019-44319 A.
[0048] Various configurations described above can be adopted. For example, the uneven shape of the nonwoven fabric 80 may be a shape in which convex portions 81 formed by the outer surface fiber layer 81 and concave portions 88 between them are arranged in a ridge-groove shape on the first surface 1A side. Similarly, the uneven shape may be a shape in which convex portions 82 formed by the outer surface fiber layer 82 and concave portions 89 between them are arranged in a ridge-groove shape on the second surface 1B side. Furthermore, the outer surface fiber layers 81, 82 may have fibers oriented in the planar direction. The wall surface 83 formed by the connecting portion 83 may have fibers oriented vertically. The outer surface fiber layer 1 that becomes the convex portion on the first surface 1A side may have two types (a first outer surface fiber layer 81A and a second outer surface fiber layer 81B) having lengths extending in different directions that intersect in a plan view of the nonwoven fabric. The multiple connecting portions 83 may be arranged along different directions that intersect in a plan view of the nonwoven fabric, and may have two types (first connecting portions 83A and second connecting portions 83B) with different wall surface orientations of the connecting portions 83. In this case, the first connecting portions 83A and the second connecting portions 83B may have wall surface orientations that are different from each other, or the fibers may be oriented vertically. This nonwoven fabric 80 typically has the shape shown in FIG. The uneven shape of the nonwoven fabric 80 is described in paragraph 2 of JP 2019-44319 A.
[0049] It can be produced by the method described in
[0057] .
[0048] The nonwoven fabric 90 (Specific Example 2) has a single layer structure containing thermoplastic fibers, and has the uneven shape shown below. That is, on the first surface 1A side, a plurality of vertical ridges 911 protruding toward the first surface 1A side in the thickness direction of the nonwoven fabric are arranged extending in one direction on the first surface 1A side in a plan view. The vertical ridges 911 are arranged side by side at intervals in another direction on the first surface 1A side in a plan view different from the one direction on the first surface 1A side. In addition, horizontal ridges 921 extending in the other direction on the first surface 1A side are arranged connecting the vertical ridges 911. The vertical ridges 911 and the horizontal ridges 921 each form a hollow convex portion. The nonwoven fabric 90 has an uneven shape in its thickness direction, which includes convex portions, concave portions, and wall surfaces 911W connecting the convex portions and the concave portions, due to the vertical ridges 911 and the horizontal ridges 921 and the concave portions 922 between them. On the first surface 1A side, the convex portions formed by the vertical rib portions 911 and the horizontal rib portions 921 have lengths extending along different directions that intersect in a plan view of the nonwoven fabric 90. In this case, the uneven shape on the first surface side of the nonwoven fabric 90 may be a shape in which the convex portions formed by the vertical rib portions 911 and the horizontal rib portions 921 and the concave portions therebetween are arranged in a ridge-groove shape. In addition, on the second surface 1B side, a plurality of hollow convex ridges 931 are arranged, which extend in one direction on the second surface 1B side in plan view and are arranged in another direction on the second surface 1B side different from the one direction on the second surface 1B side. In addition, a concave ridge 936 sandwiched between the plurality of convex ridges 931 extends in one direction on the second surface 1B side. The uneven shape on the second surface 1B side of the nonwoven fabric 90 has a shape in which the convex ridges 931 and the concave ridges 936 are arranged in a ridge-like shape. The convex ridges 931 are formed by a plurality of convex portions 934 connected in a ridge-like shape, and narrow and wide portions are alternately connected and arranged in a plan view. Between the convex portions 934 connected in a ridge-like shape, there is a slightly low depression 935. Nonwoven fabric 90 has an uneven shape in its thickness direction, which includes protrusions, recesses, and wall surfaces 931W connecting the protrusions and recesses, due to protrusions 931 and recesses 936. Further, in the convex streak portion 931, the concave streak portion 936 and the wall surface 931W, the adhesion polymer is present on the fiber surfaces, and the adhesion polymer is adhered so as to cover the fiber entanglement points. The nonwoven fabric 90 may have various configurations described in paragraphs
[0012] to
[0058] of JP 2019-44320 A. For example, the orientation direction of the fibers constituting the vertical ridge portion 911 and the fibers constituting the horizontal ridge portion 921 may be different. The height of the vertical ridge portion 911 and the height of the horizontal ridge portion 921 may be different, and the horizontal ridge portion 921 may be curved in the thickness direction of the nonwoven fabric 90 or may have an equal height. In addition, each of the two lines constituting the widthwise outline of the convex strip portion 931 when viewed in plan from the second surface 1B side may be a curve having multiple arcs. Fuzz may be arranged on the side of the convex strip portion 931. This nonwoven fabric 90 typically has the shapes shown in FIGS. Such an uneven shape of nonwoven fabric 90 can be produced by the method described in paragraphs
[0059] to
[0065] of JP2019-44320A.
[0049] The method for producing the nonwoven fabric of the present invention preferably includes a step of spraying the nonwoven fabric after forming the uneven shape as described above as a raw material nonwoven fabric with an adhesion polymer coating solution by a spray or the like, and drying it. This can prevent adhesion (sticking) between the nonwoven fabric and a mold for forming unevenness used when producing a nonwoven fabric from a fiber web. In addition, the spraying method is preferable because it allows suitable control of the amount of adhesion polymer applied to the nonwoven fabric. In the above-mentioned manufacturing method, the deposition polymer coating solution is preferably sprayed from the side of the raw nonwoven fabric where the wall surface is exposed, which is preferable because the deposition polymer is more easily and reliably fixed to the wall surface of the uneven shape of the nonwoven fabric of the present invention.
[0050] For example, the method for producing the nonwoven fabric of the present invention is preferably carried out through the steps shown in FIG. In Fig. 11 (A) and (B), a fiber web 110 containing thermoplastic fibers is placed on the support male member 120, and the support female member 130 is pressed into the support male member 120 from above the fiber web 110. At this time, the protrusion 121 of the support male member 120 is inserted into the support recess 132 of the support female member 130. Also, the protrusion 131 of the support female member 130 is inserted into the support recess 122 of the support male member 120. This causes the fibers to be oriented in the thickness direction and the planar direction. Next, as shown in Fig. 11 (C), the support female member 130 is removed, and hot air W is blown from above the shaped fiber web to fuse the fibers together. This forms a raw material nonwoven fabric 140. Thereafter, as shown in Figs. 11(D) and (E), the raw nonwoven fabric 140 is removed from the support male material 120, and the adhesive polymer coating solution 66 is sprayed with a spray or the like to fix the adhesive polymer 6, thereby obtaining the nonwoven fabric of the present invention. At this time, the surface side to which the adhesive polymer coating solution 66 is sprayed on the raw nonwoven fabric is preferably the surface side on which the wall surface in the thickness direction connecting the front and back surfaces is exposed by the shaping. This allows the adhesive polymer to be reliably attached to the wall surface. In addition, the surface side on which the wall surface is exposed is preferably the surface side 1B on which hot air is blown in Fig. 11(D). This allows the surface on which the fibers have been relatively fused by the hot air to be the surface on which the adhesive polymer is fixed, and this surface side can be the back side (the side facing the skin in an absorbent article) during use.
[0051] The drying temperature is preferably 60°C or higher, more preferably 100°C or higher, and even more preferably 110°C or higher. This makes it easier to promote the crosslinking reaction of the adhesion polymer coating agent in the sprayed adhesion polymer coating solution, and it is preferable that the strength of the fiber surface and the adhesive strength at the fusion point, and therefore the compression resistance of the nonwoven fabric, are improved. In addition, from the viewpoint of improving the texture of the nonwoven fabric, the drying temperature is preferably 130°C or lower, more preferably 125°C or lower, and even more preferably 120°C or lower. Furthermore, the drying time is preferably 1 minute or more, more preferably 3 minutes or more, and even more preferably 5 minutes or more, from the viewpoint of improving the crosslinking reaction of the polymer.
[0052] The spray mass of the adhesive polymer coating agent is set to 10 g / m per unit area of the raw nonwoven fabric in order to improve the thickness retention of the nonwoven fabric when pressed. 2 More than 20 g / m is preferable. 2 The spray mass of the adhesive polymer coating agent is preferably 300 g / m2 or less per unit area of the raw material nonwoven fabric from the viewpoint of improving production efficiency and preventing contamination of the production line. 2 Less than 250 g / m is preferable. 2 The following is more preferred: In addition, within the above range, the spray mass of the adhesion polymer coating agent can be appropriately set depending on the application of the nonwoven fabric. When the nonwoven fabric of the present invention is used for sanitary products (absorbent articles, wiping sheets, masks, etc.), the spray mass of the adhesion polymer coating agent is set to 10 g / m per unit area of the raw material nonwoven fabric from the viewpoint of improving the texture of the nonwoven fabric. 2 More than 30g / m 2 Less than 15 g / m is preferred. 2 More than 25g / m 2 When the nonwoven fabric of the present invention is used for industrial purposes such as filters, the spray mass of the adhesive polymer coating agent is preferably 100 g / m2 or less per unit area of the raw material nonwoven fabric, from the viewpoint of improving the thickness retention of the nonwoven fabric when pressed. 2 More than 300g / m 2 Less than 150 g / m 2 More than 250g / m 2 The following is more preferred:
[0053] Next, the thermoplastic fibers constituting the nonwoven fabric of the present invention will be described. The thermoplastic fibers may be any fibers that are commonly used as materials for nonwoven fabrics without any particular limitations. For example, they may be fibers made of a single resin component or composite fibers made of multiple resin components. Composite fibers may have, for example, a core-sheath structure or a side-by-side structure. When using composite fibers containing a low melting point component and a high melting point component as the thermoplastic fiber (for example, composite fibers having a core-sheath structure in which the sheath is a low melting point component and the core is a high melting point component), the temperature of the hot air blown onto the fiber web in the manufacturing process is preferably equal to or higher than the melting point of the low melting point component and lower than the melting point of the high melting point component. More preferably, the temperature is equal to or higher than the melting point of the low melting point component and lower than the melting point of the high melting point component by 10°C or more, and even more preferably, the temperature is higher than the melting point of the low melting point component by 5°C or more and lower than the melting point of the high melting point component by 20°C or more. In addition, from the viewpoint of elasticity, the more the core of the core-sheath structure composite fibers have, the higher the elasticity. Therefore, it is preferable that the core component is larger in terms of cross-sectional area ratio. A specific example of a composite fiber having a core-sheath structure in which the sheath is a low melting point component and the core is a high melting point component is a composite fiber having a core-sheath structure in which the sheath is a polyethylene resin (hereinafter also referred to as PE) and the core is a polyethylene terephthalate resin (hereinafter also referred to as PET). Furthermore, in composite fibers with a core-sheath structure, when the resin component of the sheath has a lower glass transition point than the resin component of the core (hereinafter referred to as low glass transition point resin) (for example, the resin component of the core is PET and the resin component of the sheath is PE), the thickness recovery of the nonwoven fabric can be further improved by reducing the mass ratio of the low glass transition point resin component.
[0054] Such a nonwoven fabric of the present invention can be used for various purposes. For example, the nonwoven fabric of the present invention can be used in absorbent articles such as diapers, sanitary napkins, panty liners, and urine pads. Absorbent articles typically have a liquid-permeable top sheet, a back sheet, and an absorbent sandwiched between them. The nonwoven fabric of the present invention can be particularly suitably used as a top sheet. Furthermore, the nonwoven fabric can also be used as a sheet in the gather part, an exterior sheet, or a sheet in the wing part of an absorbent article. The nonwoven fabric of the present invention can also be used as a component of an eye mask or a mask. EXAMPLES
[0055] The present invention will be described in more detail below based on examples, but the present invention is not limited thereto. In the examples, "parts" and "%" are all based on mass unless otherwise specified. In Table 1 below, "-" means that the item does not have a corresponding value, etc.
[0056] Example 1 (1) Preparation of raw nonwoven fabric First, a fiber web was produced using thermoplastic fibers of a core-sheath type (polyethylene terephthalate (PET) (core): polyethylene (PE) (sheath) = 5:5 (mass ratio)) with a fineness of 1.8 dtex. The fiber web was subjected to uneven shaping using the same male support material and female support material as in Example 1 described in JP 2019-44320 A (FIGS. 13(A) to (C) of the same document). At that time, the female support material was pressed in at 8 mm. Next, the female support was removed, and the shaped fiber web held on the male support was transported at a transport speed of 10 m / min, while hot air was blown from above the fiber web (air-through treatment) twice. The first blowing treatment was performed under conditions of a temperature of 160°C, a wind speed of 68 m / sec, and a blowing time of 5 seconds. The second blowing treatment was performed under conditions of a temperature of 160°C, a wind speed of 6.0 m / sec, and a blowing time of 5 seconds. This resulted in a fiber fineness of 1.8 dtex and a basis weight of 40±4 g / m 2 Thus, a raw nonwoven fabric having the uneven shape shown in Figures 5 to 10 was produced. The size of the raw nonwoven fabric was 100 mm x 100 mm. (2) Preparation of adhesion polymer coating solution An adhesion polymer coating solution was prepared by mixing 10% by mass of an adhesion polymer solution with a solid content of about 50% and 90% by mass of deionized water. The adhesion polymer solution used had a solid content (adhesion polymer coating agent) with a glass transition point of 60°C (Polysol AT-860 (product name) manufactured by Showa Denko K.K. Ingredients: acrylic resin 49.8% by mass, water 50.2% by mass). The adhesion polymer solution had a pH of 4.6 and a viscosity of 69 mPa·s. (3) Spraying of adhesive polymer coating solution Next, the adhesive polymer coating solution was evenly applied by spraying to the second surface 1B (hot air blowing surface) of the raw nonwoven fabric on which the convex rib portion 931 and the concave rib portion 936 were arranged as shown in Figures 8 to 10. Next, the raw nonwoven fabric was dried at 120°C for 5 minutes in an electric dryer. This produced nonwoven fabric sample A1 of Example 1 having the apparent thickness and contact area shown in Table 1. The apparent thickness and contact area were measured based on the above-mentioned (Method for measuring the apparent thickness of a nonwoven fabric under a load of 0.05 kPa) and (Method for measuring the contact area). The solid content of the polymer solution was 22.1 g / m 2 This was measured by the change in mass of the nonwoven fabric before and after application of the adhesion polymer.
[0057] Example 2 Nonwoven fabric sample A2 of Example 2 was prepared in the same manner as in Example 1, except that an attachment polymer solution having a glass transition point of 10°C (Aron NW-7060 (product name) manufactured by Toa Gosei Co., Ltd.; components: 49.9 mass % acrylic acid-based polymer, 49.6 mass % water, 0.5 mass % methanol) was used as the attachment polymer solution, and a coating method was used in which the raw nonwoven fabric was impregnated with the attachment polymer coating solution. The attachment polymer solution had a pH of 5.3 and a viscosity of 58 mPa s. The solids content of the polymer solution was 16.9 g / m 2 It was.
[0058] Example 3 Nonwoven fabric sample A3 of Example 3 was prepared in the same manner as in Example 1, except that the attachment polymer solution used was one with a glass transition point of the solid content of 15°C (Sumikaflex 752 (product name) manufactured by Sumika Chemtex Corporation; components: ethylene-vinyl acetate copolymer (concentration approximately 50%), water (concentration approximately 50%), emulsifier (undisclosed)) and the raw nonwoven fabric was impregnated with the attachment polymer coating solution. The attachment polymer solution had a pH of 5.4 and a viscosity of 1020 mPa s. The solid content of the polymer solution was 22.1 g / m 2 It was.
[0059] Example 4 Nonwoven fabric sample A4 of Example 4 was prepared in the same manner as in Example 1, except that an attachment polymer solution with a glass transition point of the solid content of 40°C (DICFINE AJ-1820 (product name) manufactured by DIC Corporation; components: 50-60 mass % water, 44.5 mass % acrylic resin, less than 1% ammonia (containing water), less than 1% others) was used and a coating method was used in which the raw nonwoven fabric was impregnated with the attachment polymer coating solution. The attachment polymer solution had a pH of 6.1 and a viscosity of 588 mPa s. The coating weight of the polymer solution solids was 16.8 g / m 2 It was.
[0060] Example 5 A nonwoven fabric sample A5 of Example 5 was prepared in the same manner as in Example 1, except that a coating method in which the raw nonwoven fabric was immersed in a polymer coating solution was used. The solids content of the polymer solution was 20.1 g / m 2 It was.
[0061] Example 6 Nonwoven fabric sample A6 of Example 6 was produced in the same manner as in Example 3, except that the coating solution was adjusted to 30 mass% of the deposition polymer solution with a solid content of about 50% and 70 mass% of deionized water. The applied amount of the solids of the adhesion polymer solution was 97.9 g / m 2 It was.
[0062] Example 7 A nonwoven fabric sample A6 of Example 6 was prepared in the same manner as in Example 3, except that an undiluted deposition polymer solution having a solid content of about 50% was used without diluting it. The solids content of the polymer solution was 331 g / m 2 It was.
[0063] Comparative Example 1 The raw material nonwoven fabric produced in Example 1 was used as nonwoven fabric sample C1 of Comparative Example 1. In other words, nonwoven fabric sample C1 had no attached polymer.
[0064] Comparative Example 2 Nonwoven fabric sample C2 of Comparative Example 2 was prepared in the same manner as in Example 1, except that the attachment polymer solution used had a glass transition point of -40°C (Boncoat AB-886 (product name) manufactured by DIC Corporation; components: 50.8% by mass of acrylic resin, 45-55% by mass of water, less than 1% by mass of n-butyl acrylate, less than 1% by mass of isopropyl alcohol, and less than 1% by mass of others) and the raw nonwoven fabric was impregnated with the attachment polymer coating solution. The attachment polymer solution had a pH of 6.6 and a viscosity of 40 mPa s. The coating weight of the solids of the polymer solution was 20.0 g / m 2 It was.
[0065] The following measurements and tests were carried out for each of the above examples and comparative examples. (1) Adhesion area and adhesion area ratio of polymer on the wall surface The measurement was performed and calculated based on the above-mentioned (Method for measuring the adhesion area ratio of the adhesion polymer on the wall surface). (2) Apparent thickness test at 3 kPa pressure The load in the above-mentioned (method of measuring the apparent thickness of a nonwoven fabric under a load of 0.05 kPa) was changed to 3 kPa, and the measurement was performed after leaving the fabric to stand for 1 minute with the load (compressive force) applied. (3) Soft stool spreading area test The top sheet of "Merry's Tape S size" (product name) manufactured by Kao Corporation was peeled off with cold spray, and the nonwoven fabric samples prepared in each Example and Comparative Example were placed as the top sheet. At that time, the surface of the nonwoven fabric sample that was to come into contact with the skin (the surface shown in FIG. 5) was placed facing up. The diaper was spread out flat, and 10 g of simulated soft stool (viscosity 40 mPa s) was injected at a flow rate of 6 g / s into the diaper, 30 mm behind the longitudinal center. The simulated soft stool was made by dispersing bentonite in ion-exchanged water, and the bentonite concentration was adjusted to a viscosity of 40 mPa s. A resin film was placed over the injection position, and a weight was placed on the resin film to apply a pressure of 3 kPa, followed by leaving the film to stand for 2 minutes. After 2 minutes, the weight and resin film were removed, and the area on the surface sheet (each nonwoven fabric sample) where the simulated soft stool had spread was transferred to an OHP sheet, scanned and imported into Image-Pro Plus (product name, manufactured by Nippon Roper Co., Ltd.) to determine the area of stool spread on the surface sheet (each nonwoven fabric sample).
[0066] [Table 1]
[0067] As shown in Table 1, the nonwoven fabric samples of each Example had the same apparent thickness as the nonwoven fabric samples of each Comparative Example, but had a greater thickness of 1.5 mm or more when pressurized with 3 kPa, and the reduction in thickness when a compressive force was applied was smaller than that of the nonwoven fabric samples of each Comparative Example. Furthermore, when the diffusion area of simulated loose stool was tested for Example 1, which had a small reduction in thickness upon compression, and Comparative Example 1, which had a large reduction in thickness, Example 1 had a smaller diffusion area than Comparative Example 1. In other words, it was found that the small reduction in thickness in Example 1 was significant in suppressing the diffusion area of body fluids such as loose stool, and was significant in the liquid absorbency of the absorbent article and in preventing body fluids from adhering to the skin. [Explanation of symbols]
[0068] 10, 20 Nonwoven fabric 12, 22 Convex part on one side 12A, 22A Top of the convex part on one side 13, 23 Convex part on the second side 13A, 23A Top of the convex part on the second side 14, 24 Wall 6. Adhesion Polymer 61 Adhesive polymer film 66 Adhesive polymer coating solution 7. Fiber 71 Sunspot L, L1~L4 reference line
Claims
1. An air-through nonwoven fabric having fusion points between fibers, The fiber has a polymer having a glass transition temperature of 10° C. or more attached thereto, The apparent thickness is 1.5 mm or more when a load of 0.05 kPa is applied from one side using a horizontal plate, On at least one side of the air-through nonwoven fabric, the ratio of the contact area between the horizontal plate and the air-through nonwoven fabric under a pressure of 3 kPa to the surface area of the air-through nonwoven fabric is 90% or less; The polymer is fixed to the surface of the fusion points between the fibers. Air-through nonwoven fabric.
2. 2. The air-through nonwoven fabric according to claim 1, which has one surface and a second surface opposite to the first surface, and the proportion of the contact area on both the first surface and the second surface is 90% or less.
3. The air-through nonwoven fabric described in claim 1 or 2, wherein the air-through nonwoven fabric has a thickness-wise wall surface connecting one side and a second side of the air-through nonwoven fabric, and the degree of longitudinal orientation of the fibers in the wall surface is 50% or more and 85% or less.
4. The air-through nonwoven fabric according to any one of claims 1 to 3, wherein the air-through nonwoven fabric has a wall surface in a thickness direction connecting one surface and a second surface of the air-through nonwoven fabric, and the adhesion area ratio of the polymer on the wall surface is 20% or more.
5. The air-through nonwoven fabric according to any one of claims 1 to 4, having an apparent thickness of 1.5 mm or more when pressurized at 3 kPa.
6. The air-through nonwoven fabric according to any one of claims 1 to 5, which is for an absorbent article.
7. An absorbent article comprising the air-through nonwoven fabric according to any one of claims 1 to 6.
8. A method for producing the air-through nonwoven fabric according to any one of claims 1 to 6, comprising the steps of spraying a polymer coating liquid containing a polymer having a glass transition point of 10°C or higher onto a raw material air-through nonwoven fabric, and drying the fabric.
9. The method for producing an air-through nonwoven fabric according to claim 8, wherein the polymer coating liquid is a liquid containing 3% by mass or more and 55% by mass or less of a polymer having a glass transition point of 10° C. or more.
Citation Information
Patent Citations
Absorptive article
JP2001187088A
Method of manufacturing nonwoven cloth, and nonwoven cloth
JP2015086501A
Crosslinkable aqueous dispersion liquid and nonwoven fabric
JP2016008358A
Fabric for disposable fiber product, and disposable fiber product and fiber sheet using same
WO2019027056A1